Analisis Penetapan Ujrah dalam Akad Rahn Tasjily Perspektif Fatwa DSN-MUI No. 68/DSN-MUI/III/2008 dan Ekonomi Syariah - Moh. Asep Zakariya Ansori; Siti Nurhalizah; Nailah Ahada Pramitha; Muhammad Najmi Nurul Hadi; Muhammad Fathir Musta’wan (As-Syirkah: Islamic Economic & Financial Journal, 2026)
Salam and Istisna' contracts are two order-based sale-purchase financing instruments within the Islamic financial system that have received legal legitimacy through DSN-MUI Fatwa No. 05/DSN-MUI/IV/2000 on Salam Sale-Purchase, Fatwa No. 06/DSN-MUI/IV/2000 on Istisna' Sale-Purchase, and Fatwa No. 22/DSN-MUI/III/2002 on Parallel Istisna'. Although both have been formally issued as fatwas for more than two decades, their utilization in the practice of Islamic financial institutions in Indonesia remains limited and has not been optimized. This study aims to analyze the substance of DSN-MUI fatwas concerning Salam and Istisna' contracts, to identify their characteristics, pillars, conditions ,and fundamental differences as Islamic financing instruments, and to formulate strategies for strengthening their implementation. The method employed is library research with a normative-juridical qualitative approach, examining DSN-MUI fatwas, classical and contemporary muamalah fiqh literature, Islamic banking regulations, and relevant scientific journals. The findings indicate that the Salam contract functions effectively as a financing instrument for the agricultural and commodity sectors, with a payment-in-advance and later-delivery mechanism, whereas the Istisna' contract is more suitable for financing the construction, property, and production-order-based manufacturing sectors. The differences between the two lie in the object of the contract, the payment mechanism, and the timing of goods delivery. This study also reveals that the weak implementation of both contracts is caused by practitioners' limited understanding, the risk of delivery default, moral hazard, and the lack of optimal synchronization between DSN-MUI fatwas and the technical regulations of the Financial Services Authority. This research recommends a risk mitigation scheme in the form of integrating Islamic agricultural insurance for Salam and third-party bank guarantees for Istisna', which is expected to contribute to strengthening the conceptual foundation for the development of Islamic financing products that favor the real and productive sectors.